Unveiling Hidden Market Manifolds : Transformer-Powered TDA with Bayesian Edge - Sheredeko, Oleksandr (2025)
This paper presents a high-frequency trading (HFT) framework designed to exploit short-term market trends. A key concept is the processing approach that employs topological data analysis to exploit volatility regimes. These refined signals are passed into a Bayesian inference model that quantifies uncertainty.